2021
DOI: 10.1002/chem.202102386
|View full text |Cite
|
Sign up to set email alerts
|

Explaining the Advantageous Impact of Tertiary versus Secondary Nitrogen Center on the Activity of PNP‐Pincer Co(I)‐Complexes for Catalytic Hydrogenation of CO2

Abstract: Pincer ligated coordination complexes of base metals have shown remarkable catalytic activity for hydrogenation/dehydrogenation of CO2. The recently reported MeN[CH2CH2(iPr2)]2Co(I)PNP‐pincer complex was shown to exhibit substantially higher catalytic activity in comparison to the corresponding catalyst, HN[CH2CH2(iPr2)]2Co(I)PNP, bearing a secondary nitrogen center on the pincer ligand. Here, we computationally investigate the mechanisms for hydrogenation of CO2 to formate catalyzed by these two Co‐PNP comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 48 publications
1
4
0
Order By: Relevance
“…149,150 There are two pathways for the Co-catalyzed CO 2 hydrogenation: one is the associative pathway in which the CO 2 reacts with the Co-metal center first and the other is the one in which hydride transfer takes place from the Co-complex to CO 2 . The most general mechanism is similar to the Fe-catalyzed CO 2 hydrogenation and reported by the Ke, 148 Pati, 148 Lu 142 and Linehan 141 groups. Accordingly, the catalytic cycle consists of the following steps: (1) the cobalt centre undergoes oxidative addition with H 2 to produce a cobalt-dihydride complex; (2) the cobalt-dihydride complex deprotonates with base or formate anions to produce the cobalt-monohydride complex (true catalytically active species) and (3) direct hydride transfer hydrogenation takes place from the cobalt-monohydride complex to hydrogenate CO 2 to produce formic acid (Scheme 4).…”
Section: Thermochemical Carboxylationssupporting
confidence: 77%
See 1 more Smart Citation
“…149,150 There are two pathways for the Co-catalyzed CO 2 hydrogenation: one is the associative pathway in which the CO 2 reacts with the Co-metal center first and the other is the one in which hydride transfer takes place from the Co-complex to CO 2 . The most general mechanism is similar to the Fe-catalyzed CO 2 hydrogenation and reported by the Ke, 148 Pati, 148 Lu 142 and Linehan 141 groups. Accordingly, the catalytic cycle consists of the following steps: (1) the cobalt centre undergoes oxidative addition with H 2 to produce a cobalt-dihydride complex; (2) the cobalt-dihydride complex deprotonates with base or formate anions to produce the cobalt-monohydride complex (true catalytically active species) and (3) direct hydride transfer hydrogenation takes place from the cobalt-monohydride complex to hydrogenate CO 2 to produce formic acid (Scheme 4).…”
Section: Thermochemical Carboxylationssupporting
confidence: 77%
“…143 Next year, Pati and co-workers compared the effect of secondary and tertiary nitrogen centers on the catalytic reactivity of the Co( i )PNP-pincer complex for CO 2 hydrogenation and found that the tertiary nitrogen bearing ligand was more reactive than the secondary nitrogen. 148…”
Section: Thermochemical Carboxylationsmentioning
confidence: 99%
“…Finally, nucleophilic pre-activation of the inherently stable CO 2 molecule via forming a covalent carbamate-like intermediate with the pendant amine before the hydride transfer may be considered (pathway C, Scheme 5). [30] This mode of CO 2 fixation mimics an active site of photosynthetic ribulose-1,5-bisphosphate carboxylase oxygenase enzyme, which reversibly binds CO 2 via NÀ C bond formation (carbamate intermediate) with a lysine residue in the secondary coordination sphere. [31] Considering that a strong base in a stoichiometric amount is required under the optimized hydrogenation conditions, the existence of the protonated species 2H + is unlikely, ruling out pathway A.…”
Section: Catalytic Studiesmentioning
confidence: 99%
“…Among various technologies, the electrocatalytic conversion of carbon dioxide provides an useful way to remove atmospheric CO 2 , thereby converting it into chemical feedstock. [1][2][3][4][5][6][7][8][9][10][11][12] Being almost inert in character, activation of the CO 2 molecule into CO 2 À , i.e., single electron activation of carbon dioxide, is a highly endergonic process with a strong negative electrochemical potential of À1.9 V vs. NHE. 13 Electrochemical reduction of CO 2 into value added chemicals or fuels provides a promising measure for encountering the anthropogenic carbon dioxide emission to build up a sustainable chemical industry.…”
Section: Introductionmentioning
confidence: 99%
“…Among various technologies, the electrocatalytic conversion of carbon dioxide provides an useful way to remove atmospheric CO 2 , thereby converting it into chemical feedstock. 1–12…”
Section: Introductionmentioning
confidence: 99%